Consumer behaviour and ICSS: exploring how consumers respond to Information, Connection and Signposting Services - Conklin, Kathy; Hyde, Richard; Parente, Fabio; Snowley, Kay (Linguistic Profiling for Professionals, University of Nottingham, 2018)
This research examines consumer behaviour when presented with search results and websites containing Information, Connection and Signposting Services ('ICSS') and provides policy recommendations aimed at ensuring that consumers are able to identify ICSS and make fully informed choices about using phone-paid service numbers to access, in particular, customer service helplines of popular service providers.